ORIGIN DESIGNATION AND PROFITABILITY FOR SMALL WINE GRAPE GROWERS: EVIDENCE FROM A COMPARATIVE STUDY - Di Vita, Giuseppe; DAmico, Mario (Economics of Agriculture, 2013)
The concept of profitability has been widely debated in the international scientific economic community but there are few studies which contribute to connecting the profitability of micro and small agro-food holdings in PDO or PGI areas with their ability to stay afloat in a competitive market. This study compares the economic results of quality wine grape producers in Sicily providing an analysis of the impact and consequences of raised economic performance in local vine-grower economies. Economic indicators were employed to compare the profitability in two PDO areas, verifying if micro and small size farm quite remain competitive in an increasingly concentrated wine market. Detailed survey data was collected in 2 of the most important Sicilian PDO wine areas, showing the first results of some economic indicators which compare the vine-growing processes in each geographic area and evaluate the profitability of a sample of small grape producers. To evaluate the remuneration of capital and the ability of smallholder to compete in a global market, average farm profitability expressed as farm net value for each homogeneous area was calculated taking into account production costs and total output. Despite several studies demonstrating that PDO certification increases costs and profits our study reveals how DO does not always ensure adequate profitability for micro and small vine growers. The production and sale of unprocessed grapes does not provide any value-added products and local producers do not gain additional remuneration for the intangible components of their PDO grapes. Further analysis has required exploring to what extent these results are caused by increasing costs or by an inefficient market structure.